PERUBAHAN PENGGUNAAN LAHAN PADA LANSKAP SAWAH TERAS DAN FAKTOR PENYEBABNYA DI HOKUDAN CHO, HYOGO PREFECTURE, JEPANG - I G.A.A. Rai Asmiwyati; Nurhayati Hadi Susilo Arifin (Environmental Research Center (PPLH) of Udayana University)
The research were identified terraced land use change and its causality aswell as analyzed the relationship with irrigation management systems in a terracedpaddy landscape in Hokudan-Cho, Awaji Island, Hyogo Prefecture, Central Japan.Between 1963 and 2000. As the result, the land use change from 1963 to 2000 wasdominated by the decrease of terraced paddy field into other utilizations. It becameclear that the social factors which cannot be seen directly in the field inducedinfluences on the pattern of landscape change and the land management in the twotypes of irrigation system. Customary social rules which is contained in Tazu systemwere strongly contributed to the sustainability of the terraced paddy fields. Hopingthis research also can be an inspiration to conserve the landscape of terraced paddyfield in Bali Island.